Upper extremity blood-flow restriction training applied during walking in an adult with a rare form of spina bifida: a case report - Gann, Elliot J.; Arriaga, Ivan; Mañago, Mark M.; Struessel, Tamara S. (Physiotherapy theory and practice, 2025)
Adults with spina bifida have impaired mobility and often rely on assistive devices like crutches for walking, which exert high torque demands on the upper extremities. Blood flow restriction training (BFRT) may improve strength and gait measures by increasing intensity of training when applied during walking for individuals with limited walking tolerance. However, no studies have investigated the application of BFRT to the upper extremities for individuals who rely on crutches for walking. This case describes a 29-year-old female with diastematomyelia, a rare form of spina bifida, who had lower extremity weakness and reduced gait capacity requiring crutches. The patient underwent 8 weeks of bilateral upper extremity BFRT during walking. The BFRT program consisted of 4 bouts of walking per session, each lasting 3 minutes with 35-50% limb occlusion pressure. Outcomes measured at baseline and 8 weeks included the 10 Meter Walk Test (10MWT), Timed Up and Go (TUG), 5 Times Sit-Stand Test (5×STS), hand-held dynamometry of 8 upper extremity muscles, and a BFRT satisfaction questionnaire. After 8 weeks, she demonstrated improvements on the 10MWT (0.15 m/s, 23%), TUG (-3.4s, 20%), 5×STS (-3.4 s, -22%), and upper extremity strength improvements ranged from 8-79% (2.8-6.7 kg). There were no adverse events related to the intervention and satisfaction was high. Bilateral upper extremity BFRT was safely applied during walking in an adult with spina bifida. The improvements in strength and functional mobility warrant future study among individuals who rely on upper extremity strength for ambulation.